Membership in Employers' Associations and Collective Bargaining Coverage in Germany - Uwe Jirjahn (Institute of Labor Economics (IZA), 2021)
While there is a strong overlap between membership in employers' associations and collective bargaining coverage, the overlap is far from being perfect. Using unique firm-level data from Germany, this study estimates the determinants of the membership in employers' associations and the coverage by industry-level or firm-level agreements. The analysis particularly focuses on the various constellations of membership and collective bargaining status. The results show that firm-level worker representation, foreign ownership, work organization, firm size, age and East-West differences are important determinants. Altogether, the analysis demonstrates that a more differentiated picture of industrial relations can be obtained by considering both membership in employers' associations and collective bargaining coverage.
Keywords: F23; F66; J51; J52; 330; employers' associations; industry-level bargaining; firm-level bargaining; foreign ownership; works councils; union density